Conflict, the paradox of power, and income redistribution: a game-theoretic analysis - Ostenberg, Ryan Heath (Kansas State University, 2020)
In this paper, we present a conflict perspective on income inequality by analyzing issues on the Paradox of Power as addressed by Hirshleifer. Specifically, we use a standard model of conflict to analyze the incentives of fighting between two parties with income disparity when conflict’s destructiveness is an endogenous function of fighting effort. We find that when destructiveness is high, the more-endowed and the less-endowed individuals are better off by reducing the costly fighting. But when the destructiveness is low, fighting for more resources becomes more severe across different parties with income disparity. We further look at how income re-distribution policies affect each party’s incentives for fighting under the shadow of conflict.
Keywords: Economics; Conflict; Paradox of Power; Game Theory; Microeconomic Theory